P09.01 Single-cell transcriptomic atlas-guided development of chimeric antigen-receptor (CAR) T cells for the treatment of acute myeloid leukemia. (21st September 2022) - Gottschlich, A; Thomas, M; Grünmeier, R; Lesch, S; Rohrbacher, L; Igl, V; Briukhovetska, D; Benmebarek, M; Dede, S; Müller, K; Xu, T; Dhoqina, D; et al.
Abstract : Background: While chimeric-antigen receptor (CAR) T cells have revolutionized the treatment of refractory B cell malignancies, they have yet to achieve success in the treatment of acute myeloid leukemia (AML). 1 In AML, development of CAR therapy is hindered by expression of AML-associated antigens also on pivotal healthy tissues (e.g. hematopoietic stem and progenitor cells, HSPC). The revolution in single-cell technologies has generated massive expression data, providing precise information on the transcriptomic anatomy of healthy and malignant cells. 2 However, these resources have rarely been used for de novo antigen predictions. We hypothesized that we could use these technologies to establish high resolution antigen projections, enabling the identification of novel target structures. Hence, we leveraged an atlas of RNA sequencing data of over 500, 000 single cells from AML patients and healthy human tissues for target identification and subsequent testing of novel target structures for CAR T cell therapy. Materials and Methods: 12 single cell data sets were harmonized and used for target prediction. Anti-murine and anti-human CAR constructs targeting the lead candidate - colony-stimulating factor 1 receptor (CSF1R) - were generated and transduced into primary murine and human T cells. AML cell lines and primary AML samples were used to verify expression of CSF1R and as target cell lines in vitro and in vivo . Off-target toxicities of CAR were analyzed in vitro and in vivo using a variety of different models. Results: Using a newly developed single-cell RNA sequencing-based screening algorithm, CSF1R was identified as a promising target antigen for CAR T cell therapy in AML. Expression of CSF1R was verified on a large panel of AML cell lines and in primary AML samples. Newly developed anti-CSF1R-CAR T cells efficiently lysed AML target cells in vitro. In vivo, anti-CSF1R-CAR T cells induced strong and sustained remissions in cell line- and patient-derived xenograft models. Compared to anti-CD33-CAR T cells, anti-CSF1R-CAR T cells did not lyse healthy HSPC and proved to be safe when used in fully syngeneic mice models. Conclusions: Aided by our screening algorithm, we identified CSF1R as a new promising target for CAR therapy in AML and proved the efficacy of newly developed CAR T cells. Our results highlight the remarkable translational potential of unbiased, high-resolution target screenings for cancer entities and warrant further clinical investigations of newly developed anti-CSF1R-CAR T cells. References: Cummins, K.D. and S. Gill, Chimeric antigen receptor T-cell therapy for acute myeloid leukemia: how close to reality? Haematologica 2019; 104 (7): p. 1302–1308. Papatheodorou, I., et al., Expression Atlas update: from tissues to single cells. Nucleic Acids Res, 2020. 48 (D1): p. D77-D83. Disclosure Information: A. Gottschlich: None. M. Thomas: None. R. Grünmeier: None. S. Lesch: None. L. Rohrbacher: None. V. Igl: None. D. Briukhovetska: None. M. Benmebarek: None. S. Dede: None. K. Müller: None. T. Xu: None. D. Dhoqina: None. Ö. Umut: None. F. Märkl: None. S. Robinson: None. A. Sendelhofert: None. H. Schulz: None. B. Vick: None. B.L. Cadilha: None. R. Brabenec: None. N. Röder: None. F. Rataj: None. M. Nüesch: None. J. Wellbrock: None. F. Modemann: None. W. Fiedler: D. Speakers Bureau/Honoraria (speakers bureau, symposia, and expert witness); Modest; Amgen, Gilead, Jazz Pharmaceuticals, Servier, Daiichi Sankyo, Novartis, Abbvie, Pfizer, Amgen. F. Consultant/Advisory Board; Modest; Amgen, ARIAD/Incyte, Pfizer, Novartis, Jazz Pharmaceuticals, Morphosys, Abbvie, Celgene, Stemline, Clinigen. C. Kellner: None. T. Herold: None. D. Paquet: None. I. Jeremias: None. L. von Baumgarten: None. S. Endres: B. Research Grant (principal investigator, collaborator or consultant and pending grants as well as grants already received); Significant; TCR2. E. Ownership Interest (stock, stock options, patent or other intellectual property); Modest; Carina Biotech Ltd. E. Ownership Interest (stock, stock options, patent or other intellectual property); Significant; TCR2. F. Consultant/Advisory Board; Modest; Gilde Healthcare. M. Subklewe: B. Research Grant (principal investigator, collaborator or consultant and pending grants as well as grants already received); Significant; Amgen, BMS, Gilead, Miltenyi, MorphoSys, Novartis, Roche, Seattle Genetics. D. Speakers Bureau/Honoraria (speakers bureau, symposia, and expert witness); Modest; Amgen, BMS, Gilead, Novartis, Pfizer, Takeda. F. Consultant/Advisory Board; Modest; Amgen, BMS, Gilead, Janssen, Novartis, Pfizer, Seattle Genetics, Takeda. C. Marr: None. S. Kobold: B. Research Grant (principal investigator, collaborator or consultant and pending grants as well as grants already received); Significant; TCR2 Inc. D. Speakers Bureau/Honoraria (speakers bureau, symposia, and expert witness); Modest; BMS, GSK, Novartis. E. Ownership Interest (stock, stock options, patent or other intellectual property); Modest; Carina Biotech Ltd. E. Ownership Interest (stock, stock options, patent or other intellectual property); Significant; TCR2. F. Consultant/Advisory Board; Modest; Tabby therapeutic ltd, TCR2 Inc. F. Consultant/Advisory Board; Significant; Novartis.